Trakcija pri obravnavi bolečine v križu - Lukšič-Gorjanc, Mateja (Rehabilitacija (Ljubljana), 2020)
Introduction: There are several methods for the management of low back pain, including traction. The purpose of this preliminary study was to review the results of traction therapy with a forward bend test, which is used regularly in clinical practice at the Dolenjske Toplice Spa. We also examined the effects of age and the number of therapies on the results. Method: We reviewed the medical records of the patients who had undergone traction treatment on a GammaSwing device. Results: Twenty patients with chronic low back pain were included in the study, with an average age of 50 years; 13 (65 %) were women and 7 (35 %) were men. The patients received one to six therapies, after which their forward bend improved from 1 to 22 cm (9.8 cm on average). Conclusion: Improvement at the forward bend test was observed in patients who had undergone traction therapy with vibration. Age might be an associated factor. Better-designed studies are needed to verify the effectiveness of traction treatment.
Keywords: bolečina; bolečina v križu; fizioterapija; hrbtenica; test predklona; trakcija; vibracija